Addition of Fe3O4 as electron mediator for enhanced cementation of Cd2+ and Zn2+ on aluminum powder from sulfate solutions and magnetic separation to concentrate cemented metals from cementation products. Issue 6 (December 2021) - Choi, Sanghyeon; Jeon, Sanghee; Park, Ilhwan; Ito, Mayumi; Hiroyoshi, Naoki
Abstract: The zinc leach residues (ZLRs) generated by Zn hydrometallurgical process are disposed of in landfills due to a lack of proper treatment methods although they contain toxic heavy metals like Cd and Zn. To remove these heavy metals, this study investigated cementation using aluminum (Al) together with magnetite (Fe3 O4 ) from sulfate solutions. Cementation using only Al could not remove Cd 2+ and Zn 2+ because the insulating Al oxide (Al2 O3 ) layer on Al surface was not removed at high pH (5.0) from sulfate solution, and inhibiting electron transfer from Al to metal ions. The addition of Fe3 O4, however, enhanced the cementation of Cd 2+ and Zn 2+ from 0% to 83% and 92%, respectively. The results of SEM-EDS analysis for the cementation products confirmed that Cd and Zn were deposited on Fe3 O4 attached on Al surface. Electrochemical impedance spectra for Al electrode in sulfate solutions confirmed that charge transfer resistance decreased when Fe3 O4 powder was attached on the electrode surface, suggesting that Fe3 O4 acts as a mediator to enhance electron transfer from Al to metal ions in solutions. By applying magnetic separation for the cementation products, the majority of cemented Cd and Zn were recovered together with Fe3 O4 in magnetic fraction, and they were separated from Al in non-magnetic fraction. Graphical Abstract: ga1 Highlights: Enhanced cementation of Cd 2+ and Zn 2+ using Fe3 O4 and Al 0 was investigated. Without Fe3 O4, cementation efficiency of Cd 2+ and Zn 2+ was 0%. With Fe3 O4, cementation efficiencies were enhanced. Fe3 O4 acts as a mediator to enhance electron transfer from Al to metal ions. A significant portion of cemented Cd and Zn were recovered in magnetic fractions.